Understanding the objectives of the Qur’an: a critical analysis al-Ghazali's views - Gilani, Sayyid Mohammad Yunus; Islam, Tazul (Zes Rokman Resources, 2016)
‘Objectives of the Qur’an’ was pioneered by Abu Hamid Al-Ghazali in his later composition called Jawahir al-Qur’an. This particular concept becomes increasingly fashionable in the contemporary Quranic scholarship. Though it has been able to draw a particular attention from contemporary scholars, they seem reluctant to deal with al-Ghazali’s enterprise which lays cornerstone for this subject. This existing gap of study provokes exploring this subject, its theoretical basis and implications. Hence, this research aims to explore various dimensions of this gap by exploring critically the conceptual background of al-Ghazālī’s theory of objectives of the Qur’an. This research finds out that the entire discourse of the theory ‘objectives of the Qur’an’ remains focused on understanding the Qur’an. It is expected that this study may set a new direction to debate in this connection.